Infections risks of medical buildings: Perspectives investigation in a case-study - Parsia, Yasaman; Sorooshian, Shahryar; Panjehpour*, Mohammad (Diva Enterprises Pvt Ltd, 2019)
Each medical building has a significant role in presenting high quality of health services for public, so, attention to medical risks, such as, Hospital Acquired Infections (HAIs) is essential. therefore, this article attempts to describe the HAIs situations of a medical building in the Middle East and mention some medical building's factors which have role in increasing the rate of HAIs risks. The unstructured interviews with experts of the case were conducted. Based on the results, the medical building involves about HAIs like the other medical buildings and some factors, such as, poor personal hygiene can increase the rate of HAIs in the case. Any document like this article can be a useful evidence to nominate health risks, like HAI, in different medical buildings and remark issues which are relevant to decrease the rate of health risks in the other medical buildings. It can help to improve the quality of the health services and can give new ideas to the researchers and practitioners to find solutions in various fields to decline the risks of different medical errors, specially HAIs.